(untitled) - Wong, Yoyce Y. (London, 2007)
When medical devices must work inside the body, their materials are the most significant aspects of their design. In addition, industries demand that such devices are reliable, economical and compatible with the environment into which they are placed. These articles provide general overviews of various materials found to be of use in bioengineering and medicine, including ceramics, polymers and synthetic polymers, metals, composites and biodegradable hydrogels. It also covers biomaterials including tissue-derives biomaterials such as collagen, soft and hard tissue replacements, and a new chapter for this edition on controlling and assessing cell-biomaterial interactions at the micro- and nano-scale, especially in tissue engineering. Each article includes references.
Keywords: Biomedical materials,Biocompatible Materials -- chemistry,Prosthesis Implantation -- methods.,Y khoa